Development of 3D Math AR Applications as Mathematics Learning Media Augmented Reality Based - Sarah Nadya Putrie; Muhammad Noor Sulaiman Syah (Institut Agama Islam Negeri (IAIN) Salatiga, 2023)
This study aims to find out the application of 3D Math AR learning as Augmented Reality-based mathematics media in Class VIII Flat-Side Building Materials at SMPIT Nidaul Hikmah. This type of research is research and development (Research and Development) using the ADDIE development model. This research stage is limited to the implementation stage with limited testing, has not yet reached the testing stage with a broad scale of the Covid-19. The data collection technique used was a questionnaire that was distributed to 1 Mathematics Subject teacher and 10 Class VIII students at SMPIT Nidaul Hikmah. Based on a limited test conducted using a Likert measurement scale, the results of media expert validation with an average of 4.5 are in the very good category, while material experts with an average of 4 are in a good category, so that the cumulative results of the assessment by media experts and material experts an average of 4.25. Practical of learning media assessed by and teachers got an average result of 4,325 in the Very Good category. After being declared valid and practical, it can be concluded that the 3D Math AR application is feasible to use.